ANALISIS MODAL SOSIAL ANGGOTA KELOMPOK WANITA TANI DALAM PROGRAM MODEL KAWASAN RUMAH PANGAN LESTARI (M-KRPL) DI DESA TUALANG KECAMATAN TUALANG KABUPATEN SIAK - Ramansyah, Farid; Sayamar, Eri; Yulida, Roza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study is to identify of the social capital, and progam implementation problems that faced KWT members in M-KRPL program in Tualang village. The survey method was used in the study, while Simple Random Sampling was also used as the sampling technique. The number of respondents were 28 samples. The samples was taken of the KWT Cendana Wangi members who followed M-KRPL program in Tualang village. The analysis of social capitaland problem KWT members that faced in the program implementation of this study was descriptive method. The analysis social capital members used questionnaire, Scale of Likerâ€™s Summated Rating (LSR) was used. The result showed the analysis of social capital KWT members was categorized as â€high levelâ€ with the score 3,82. Social capital that high on KWT Cendana Wangi members be supported the high score existing on the social capital elements namely, participation in the social networks, reciprocal, trust, and adherence to norms, values and proactive measures. The problems that faced KWT members in the program implementation of the M-KRPL program namely, problems of production facilities, water issues, and disclosure issues. Keywords: Social Capital, Sustainable Food Houses Region, Sustainable Food Houses, Women Farming Group.